A ten-year retrospective review of maternal cardiac arrest: Incidence, characteristics, causes, and outcomes in a tertiary-care hospital in a developing country - Patchareya Nivatpumin; Tripop Lertbunnaphong; Doungdalad Dittharuk (Elsevier, 2021)
Objective: Maternal cardiac arrest is rare. We retrospectively reviewed and reported (1) the incidence of maternal cardiac arrests during admissions for delivery; (2) the characteristics and causes of cardiac arrest; and (3) the mortality rate and outcomes in a referral, single-university, teaching hospital in Thailand. Materials and methods: Data on 23 cardiac arrests during admissions for delivery in the decade January 2006-December 2015 were retrospectively chart-reviewed. Patients with gestational ages under 24 weeks or cardiac arrests and death occurring before hospital arrival were excluded. The clinical characteristics of the arrests and outcomes were collected. Results: Of 89,368 deliveries during the decade, 23 women suffered cardiac arrest (incidence, 1:3885), with 3 of those arrests occurring before delivery (incidence, 1:29,789). One patient underwent a perimortem cesarean delivery in the operating theatre. The most common reasons for the arrests were hypertension during pregnancy and cardiovascular causes (30.4% and 21.7%, respectively). Amniotic fluid embolisms were suspected for 2 patients (8.7%) with unidentified causes. The incidence of maternal deaths in peripartum cardiac arrests was 20/23, representing 86.9% (95% CI, 67.9-95.5) or 1:4468 of deliveries. Three patients suffering cardiac arrests after delivery survived to discharge. Conclusions: We found a high maternal mortality rate following cardiac arrests during hospitalization for delivery. To decrease the incidence of arrests during the peripartum period and diminish the maternal mortality rate, identification of the causes and precipitating factors is vital. High-risk pregnant women require multidisciplinary care to improve the survival-to-discharge rate.